In vivo embryo production and recovery in lacaune ewes after imposing a superovulation treatment regimen is related to pFSH dose - Figueira, Lucas Machado; Alves, Nadja Gomes; Rosa e Silva Maia, Ana Lucia; Goncalves Souza-Fabjan, Joanna Maria; Tavares Pereira Batista, Ribrio Ivan; Arrais, Aline Matos; Lima, Renato Ribeiro; Franco Oliveira, Maria Emilia [UNESP]; Fonseca, Jeferson Ferreira (Elsevier B.V., 2020)
This study was conducted to assess effects of different doses of pFSH on follicular recruitment, superovulatory response, ova/embryo recovery, and embryo yield in lactating ewes. Ewes (n = 24) had a superovulation treatment regimen imposed. All ewes were implanted with a progesterone intravaginal device for 9 d, and administered either 100 (G-100) or 200 (G-200) mg pFSH, proportioned into six doses administered at 12-h intervals, starting 60 h before device removal. At 7 days subsequent to progesterone device removal, there were non-surgical embryo recoveries (NSER) from ewes having three or more corpora lutea. At the time of the first pFSH injection, number of antral follicles were similar (P < 0.05) between ewes in the G-100 and G-200 group, however, there were more 3.1-4.0 mm follicles in ewes of the G-200 than G-100 group at the time of the second pFSH administration. Estrous response and CL number were less (P < 0.05) in ewes of the G-100 (66.7 % and 2.6 +/- 0.7) than G-200 (91.7 % and 11.6 +/- 1.2) group. There were embryo collections from 100 % and 90.9 % of ewes in the G-100 and G-200 groups, respectively (P > 0.05). Viable embryo numbers and ova/embryo recovery rate were greater (P < 0.05) in ewes of the G-200 (6.9 +/- 1.1 and 67.8 %) than G-100 (1.0 +/- 0.5 and 27.6 %) group. A dose of 200 mg pFSH was more effective in inducing a superovulatory response and embryo yield after NSER in ewes, however, the 100 mg dose was insufficient for these purposes.
Keywords: Dairy sheep; Gonadotropins; MOET; Transcervical; Uterine flushing